Pemanfaatan Game Edukasi Pada Penyuluhan PHBS di SD Glagahwero 2 Jember - Faiqatul Hikmah; Yoswenita Susindra; Iwan Abdi Suandana; Dhyani Ayu Perwiraningrum; Ria Chandra Kartika (Indonesian Journal Publisher, 2023)
Improving your health status can be done by getting used to living a clean and healthy lifestyle. The Clean and Healthy Living Behaviour (CHLB) must be promoted in school health programs related to personal hygiene and environmental sanitation to prevent disease in the school environment. Getting students used to practicing PHBS at school can be used as a foundation for health behaviour. This community service activity was carried out at SD Glagahwero 2 Jember which was attended by all students from class 1 to class 6. Education was carried out through counselling by providing explanations about how PHBS should be applied in daily life both at home, school and other public places. As well as explaining the benefits of implementing CHLB which are applied in everyday life. After counselling on the snakes and ladders educational game, students are trained to be able to answer or make decisions according to the problems/questions given in the game. The increase in knowledge that students receive about CHLB can be seen from the students' ability to answer questions correctly, this will support students' clean and healthy living habits so that they can improve the level of health in society.